Efficient System for Directed Integration into the Lactobacillus acidophilus and Lactobacillus gasseri Chromosomes via Homologous Recombination - Russell, W. M. (American Society for Microbiology, 2001)
An efficient method is described for the generation of site-specific chromosomal integrations in Lactobacillus acidophilus and Lactobacillus gasseri. The strategy is an adaptation of the lactococcal pORI system (K. Leenhouts, G. Venema, and J. Kok, Methods Cell Sci. 20:35–50, 1998) and relies on the simultaneous use of two plasmids. The functionality of the integration strategy was demonstated by the insertional inactivation of the Lactobacillus acidophilus NCFM lacL gene encoding β-galactosidase and of the Lactobacillus gasseri ADH gusA gene encoding β-glucuronidase.